CONSIDERING CORPORATE LIQUIDITY MANAGEMENT IN THE CONTEXT OF THE WORLD ECONOMY FAILING - Abdul Rosid (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Amid rising global economic uncertainty, corporate liquidity management is emerging as an urgent arena for academic and practical investigation. This study explores how liquidity management systems, as the frontline in mitigating financial pressures, are adjusted by companies to navigate real and potential economic fluctuations. Through the lens of financial analysis and risk management theory, this study can present a comprehensive design that details the adaptive and reactive strategies applied by companies in response to global market dynamics. The research method is literary study. The results of this study show that in the face of uncertainty, companies that manage their liquidity successfully adopt a holistic approach that not only defensively keeps cash sufficient to meet short-term obligations, but also proactively seizes opportunities and risks within the broader risk management framework. This research contributes to existing literature by providing contemporary insights into liquidity management practices, while offering valuable insights to stakeholders in the financial sector on how navigation of liquidity competence can be used as a strategic tool in responding to market instability. Thus, we reinforce the understanding that effective liquidity management is key to corporate sustainability in changing economic conditions.